Metaphorical Representation of Men in Pakistani Fiction: A Study of Hamid’s Moth Smoke - Tehreem Ijaz; Dr. Muhammad Yousaf (University of Chitral Journal of Linguistics and Literature, 2022)
The purpose of conducting this study is to investigate the conceptual metaphors used for men in Pakistani society and highlight the conceptualization of male gender prevailing in Pakistan. I have used Conceptual Metaphor Theory (CMT) as the theoretical framework of this study and the method of Content Analysis has been followed in order to conduct this research work. The famous novel Moth Smoke by Mohsin Hamid serves as the sample of this research work for the reason that it has been written within the Pakistani context and therefore, is considered to be a good source of the required data. The obtained data shows that male gender is held responsible for earning money and feeding the whole family. Moreover, they are at liberty to live independently and spend a self-centred life. The results of the present work may prove to be helpful for the future researchers studying the role of conceptual metaphors in the conceptualization of gender prevailing in a society as well as their significance in literature for representing gender.